HAM dan Penegakan Hukum Terhadap Tindak Pidana Perdagangan Orang - Faturohman Faturohman; Sulis Suhartini; Robiatul adawiyah (Pusat Riset dan Inovasi Nasional, 2024)
Human trafficking is a very serious violation of human rights which includes using someone through fraud, coercion, prostitution, slavery, organ harvesting and even coercion for work purposes. Handling human trafficking really requires a comprehensive legal framework and policyy implementation at the of national and international levels. But sometimes in the process of its journey it often goes through challenge after challenge in law enforcement and victim protection is still the main obstacle factor that must continue to be fought and efforts Sustainable cross-border collaboration and the role of international organizations are important drivers in enforcing effective prevention of human trafficking. The role of laws and regulations in countries including Indonesia has not yet become an important basis for preventing human trafficking.